(untitled) (Eurasian Journal of Engineering and Technology, 2022)
This article shows the role and practical significance of the subject of descriptive geometry in the development of spatial imagination and thinking of students. It describes the content of issues of varying complexity that require study and creative search for solutions to positional problems in the geometry of the drawing.